Properties of wood plastic composites (Wpc) from Batai Spp. (Paraserianthes Falcataria) / Jamaludin Kasim ... [et al.] - Kasim, Jamaludin; Abdullah, Nor Hidayani; Mohd Akhir, Suria; Sarmin, Siti Noorbaini; Mohammed, Noorshashillawati Azura (2013)
The woods of Batai spp. (Paraserianthes falcataria) were harvested from Dong Hwa MDF Factory in Merbok. Kedah. Three trees with DBH of 20-30cm were chipped and then grounded into sawdust. The sawdust and polypropylene (PP) were blended and mixed together using a dispersion mixer at a temperature of about 180 C. Composite boards were then produced and tested for their mechanical and physical strength in accordance to ASTM Standards. MAPP shows significant effect on MOE, TS and WA. PS showed a significant effect on FMOR, FMOE, Impact, WA and impact value while no significant effect on TMOR, TMOE and TS. The highest value of FMOR and FMOE was shown by particle size 75 um. No significant different in FMOR for WPC with MAPP or without MAPP. The effect of MAPP on water absorption (WA) and thickness swelling (TS) was shown to be significant. In conclusion, batai sawdust can be used as raw material in the manufacture of wood plastic composite.